Тактика лікування артеріо-венозної мальформації головного мозку під час вагітності - Литвак, С. О.; Литвак, О. О. (Clinical Endocrinology and Endocrine Surgery, 2009)
Results of treatment of 17 patients with arteriovenous brain malformation are shown. Clinical manifestation was in 15 women in II trimester of pregnancy and in 2 women in III one. In all cases lives of mother and child were preserved with minimal further disorders after microsurgical hematoma removal. Active surgical tactics of treatment is recommend ed for this category of patients.